Use the principle of induction to prove that for all n .
Answers
Step-by-step explanation:
Given: 1 + 3 + 5 + ..... + (2n - 1) = n².
Let the given statement be P(n). Then,
P(n) = 1 + 3 + 5 + ... + (2n - 1) = n²
Substitute n = 1 in the given statement, we get
LHS: [2(1) - 1)] = 1
RHS: (1)² = 1
So, the statement holds for n = 1.
Let P(k) be true.
P(k) = 1 + 3 + 5 + .... + (2k - 1) = k²
For P(k + 1),
LHS = 1 + 3 + 5 + ... + (2k - 1) + (2(k + 1) - 1)
= k² + (2k + 2 - 1)
= k² + 2k + 1
= (k + 1)²
∴ P(k + 1) is true, whenever P(k) is true.
Hence, by the principle of induction, P(n) is true for all n ∈ N.
Hope it helps!
Answer:
ʜᴇʏᴀ
Step-by-step explanation:
Given: 1 + 3 + 5 + ..... + (2n - 1) = n².
Let the given statement be P(n). Then,
P(n) = 1 + 3 + 5 + ... + (2n - 1) = n²
Substitute n = 1 in the given statement, we get
LHS: [2(1) - 1)] = 1
RHS: (1)² = 1
So, the statement holds for n = 1.
Let P(k) be true.
P(k) = 1 + 3 + 5 + .... + (2k - 1) = k²
For P(k + 1),
LHS = 1 + 3 + 5 + ... + (2k - 1) + (2(k + 1) - 1)
= k² + (2k + 2 - 1)
= k² + 2k + 1
= (k + 1)²
∴ P(k + 1) is true, whenever P(k) is true.
Hence, by the principle of induction, P(n) is true for all n ∈ N.